Grafting Influence on Physio-chemical Characters of Tomato on Brinjal Root Stock - Singh, Lovpreet; Singh, Paramjit; Jyoti; Singh, Jatinder (International Journal of Bio-resource and Stress Management, 2019)
The field experiment was conducted in research farm at Lovely Professional University, Punjab, India during 2018–2019 under protected cultivation. The objective of the study was to assess the influence of tomato grafting on rootstock of Brinjal cv. Navkiran. Tomato growers’ farmers who wants to earn supplementary from tomato harvested during rains, may find this knowledge valuable. Even the hobbyist growers may find this tomato grafting technology, enjoyable, as they continuously plant tomatoes for easy and accessible fresh tomato yields during year. The tomato cultivars used as scions were Punjab Varkha Bahar-4, Sona NTH-2829 and Heemshikhar. For tomato scion variety taken was of an indeterminate type wherein trellis was provided for favorable development. Cleft grafting technique was practised during grafting of research field work. Obtained fruits were evaluated on the basis of physio-chemical characteristics of grafted and non-grafted plants viz. fruit weight, average fruit weight, firmness, TSS, Vitamin C and titrable acidity. A positive and significant influence of grafting practice was recorded in fruits of tomato with brinjal as a rootstock. Results of this experiment confirmed that grafting of tomatoes on eggplant rootstock performed better in comparison to non-grafting ones in terms of physico-chemical traits of the produced fruit. Grafting operation could be a valuable alternative in tomato production.